A disease‐specific metabolic imaging marker for diagnosis and progression evaluation of semantic variant primary progressive aphasia. (7th July 2021) - Lu, Jiaying; Huang, Lin; Lv, Yingru; Peng, Shichun; Xu, Qian; Li, Ling; Ge, Jingjie; Zhang, Huiwei; Guan, Yihui; Zhao, Qianhua; Guo, Qihao; Chen, Keliang; et al.
Abstract: Background and purpose: The diagnosis and monitoring of semantic variant primary progressive aphasia (sv‐PPA) are clinically challenging. We aimed to establish a distinctive metabolic pattern in sv‐PPA for diagnosis and severity evaluation. Methods: Fifteen sv‐PPA patients and 15 controls were enrolled to identify sv‐PPA‐related pattern (sv‐PPARP) by principal component analysis of 18 F‐fluorodeoxyglucose positron emission tomography. Eighteen Alzheimer disease dementia (AD) and 14 behavioral variant frontotemporal dementia (bv‐FTD) patients were enrolled to test the discriminatory power. Correspondingly, regional metabolic activities extracted from the voxelwise analysis were evaluated for the discriminatory power. Results: The sv‐PPARP was characterized as decreased metabolic activity mainly in the bilateral temporal lobe (left predominance), middle orbitofrontal gyrus, left hippocampus/parahippocampus gyrus, fusiform gyrus, insula, inferior orbitofrontal gyrus, and striatum, with increased activity in the bilateral lingual gyrus, cuneus, calcarine gyrus, and right precentral and postcentral gyrus. The pattern expression had significant discriminatory power (area under the curve [AUC] = 0.98, sensitivity = 100%, specificity = 94.4%) in distinguishing sv‐PPA from AD, and the asymmetry index offered complementary discriminatory power (AUC = 0.91, sensitivity = 86.7%, specificity = 92.9%) in distinguishing sv‐PPA from bv‐FTD. In sv‐PPA patients, the pattern expression correlated with Boston Naming Test scores at baseline and showed significant increase in the subset of patients with follow‐up. The voxelwise analysis showed similar topography, and the regional metabolic activities had equivalent or better discriminatory power and clinical correlations with Boston Naming Test scores. The ability to reflect disease progression in longitudinal follow‐up seemed to be inferior to the pattern expression. Conclusions: The sv‐PPARP might serve as an objective biomarker for diagnosis and progression evaluation. Abstract : We identified a disease‐specific metabolic imaging marker for diagnosis and progression evaluation of semantic variant primary progressive aphasia with 18 F‐fluorodeoxyglucose positron emission tomography based on principal component analysis for the first time. This biomarker showed similar topography, equivalent discriminatory power, and clinical correlations with Boston Naming Test scores to the conventional voxelwise analysis, whereas its ability to reflect disease progression in longitudinal follow‐up seemed to be better.